PENGARUH KOMUNIKASI PERSUASIF TERHADAP KONSENTRASI BELAJAR SISWA (Studi Pada Siswa Kelas XII Kompetensi Keahlian Otomatisasi dan Tata Kelola Perkantoran Mata Pelajaran Otomatisasi dan Tata Kelola Kepegawaian di Sekolah Menengah Kejuruan Yayasan Pendidikan dan Kebudayaan Karya Pembangunan Bandung) - Ramadhanis Sucianci, - (2022)
The purpose of this study was to analyze the effect of persuasive communication on student learning concentration. The research method used is a survey. The research was conducted by census of 40 students of class XII Expertise Competence in Office Automation and Governance in the Subject Automation and Personnel Governance (OTKP) at the Vocational High School (SMK) Yayasan Pendidikan dan Budaya Karya Pembangunan Bandung, as respondents. The data collection technique used a 5 scale rating scale questionnaire. The data analysis technique used regression. The results showed that: (1) persuasive communication has been implemented by the teacher effectively; (2) students' learning concentration is in the high category; (3) persuasive communication has a significant effect on students' learning concentration. Step for increase the concentration of student learn is to apply persuasive communication to teachers for students that is effective in the study process.